Strategi Dakwah Dalam Mengatasi Patologi Sosial Dalam Pengatasan Penyakit Masyarakat Di Desa Kampung Melayu Kecamatan Bermani Ulu Kabupaten Rejang Lebong - Nur Cholis (Institut Agama Islam Negeri (IAIN) Curup, 2022)
From the phenomenon that researchers saw in Kampung Melayu Village, Bermani Ulu District, Rejang Lebong Regency, that the problem of community disease faced by the da'i in developing Islamic da'wah, especially in the village of Kampung Melayu. The da'i in developing da'wah still find it difficult what strategy to give in dealing with situations like this. Moreover, the media they have are still inadequate, they have not mastered many da'wah methods, especially the material which only explains the problem of prayer or other worship that has never been associated with worldly material such as poverty. The methodology used by the researcher is descriptive qualitative method. This approach is used because the data needed by the author is only in the form of information, explanations, and verbal information. The results of the study can be concluded that the disease of the community in the village of Kampung Melayu, Bermani Ulu District, Rejang Lebong Regency, there are several kinds, such as gambling, crime, liquor and there is also the use of illegal drugs. The da'i strategy to overcome the ills of the community in Kampung Melayu, Bermani Ulu District, Rejang Lebong Regency, carried out by the da'i is by discussing to increase religious knowledge and also inviting preachers from the city of Curup and its surroundings when there is a commemoration of Islamic holidays and forming TPQ which is followed by many children, if the researcher relates it to the theory of the da'wah strategy used is sentimental with a discussion approach.